2013
DOI: 10.1261/rna.037424.112
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sensors ensure guide strand selection in human RNAi pathways

Abstract: Small RNAs guide RNA-induced silencing complexes (RISCs) to bind to cognate mRNA transcripts and trigger silencing of protein expression during RNA interference (RNAi) in eukaryotes. A fundamental aspect of this process is the asymmetric loading of one strand of a short interfering RNA (siRNA) or microRNA (miRNA) duplex onto RISCs for correct target recognition. Here, we use a reconstituted system to determine the extent to which the core components of the human RNAi machinery contribute to RNA guide strand se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 59 publications
(75 reference statements)
4
109
0
2
Order By: Relevance
“…Although the mechanisms of strand selection are still not fully understood, the thermodynamic stability at the ends of a miRNA duplex was shown to be a major factor (Khvorova et al 2003;Schwarz et al 2003). In addition, both the 5 ′ nucleotide of the miRNA and Dicer-associated proteins also influence strand selection (Frank et al 2010;Noland and Doudna 2013). Upon association with AGO, the miRNA then guides RISC to target mRNAs via partial sequence complementarity, which results in translational repression and mRNA turnover (Bazzini et al 2012;Djuranovic et al 2012).…”
mentioning
confidence: 99%
“…Although the mechanisms of strand selection are still not fully understood, the thermodynamic stability at the ends of a miRNA duplex was shown to be a major factor (Khvorova et al 2003;Schwarz et al 2003). In addition, both the 5 ′ nucleotide of the miRNA and Dicer-associated proteins also influence strand selection (Frank et al 2010;Noland and Doudna 2013). Upon association with AGO, the miRNA then guides RISC to target mRNAs via partial sequence complementarity, which results in translational repression and mRNA turnover (Bazzini et al 2012;Djuranovic et al 2012).…”
mentioning
confidence: 99%
“…Complementing early notions that strands with a lower 5′ thermodynamic stability are preferentially incorporated into RISC (17)(18)(19), recent data now suggest that many other parameters, such as the position of the loop, the sequence and structure of the stem, the relative abundance of different Argonaute proteins, or competitive Argonaute-2 binding of the 5′ nucleotide of either strand, influence strand selectivity (12,14,15,20). Moreover, there is ongoing controversy over whether Dicer and associated proteins are required or dispensable for asymmetric RISC loading (21)(22)(23). No matter the exact mechanism, it is clear that off-targeting is unintended in the context of RNAi applications and must be alleviated.…”
mentioning
confidence: 99%
“…While the two strands of Drosophila miRNA duplexes are loaded by different Argonaute proteins (Okamura et al 2009;Ghildiyal et al 2010), a similar Argonaute protein-specific miRNA strand sorting mechanism has not been demonstrated in mammalian cells. Considering past studies showing that the fate of each of the two strands in the miRNA duplex is influenced by its thermodynamic stability (Khvorova et al 2003) and its interaction with Ago2 and Dicer when complexed with trans-activation response RNA-binding protein (TRBP) or protein activator of PKR (PACT) (Noland and Doudna 2013), strand selection is an attractive candidate for a temperature-sensitive step in miRNA processing. We found that the mature duplex forms of temperature-responsive miRNAs tended to have higher predicted stability and more asymmetry in stability than other miRNAs in their respective clusters and the temperature-responsive strands represented the usually less abundant strand (Noland and Doudna 2013).…”
Section: Figure 5 Functional Analysis Of the Pkcαmentioning
confidence: 99%
“…Considering past studies showing that the fate of each of the two strands in the miRNA duplex is influenced by its thermodynamic stability (Khvorova et al 2003) and its interaction with Ago2 and Dicer when complexed with trans-activation response RNA-binding protein (TRBP) or protein activator of PKR (PACT) (Noland and Doudna 2013), strand selection is an attractive candidate for a temperature-sensitive step in miRNA processing. We found that the mature duplex forms of temperature-responsive miRNAs tended to have higher predicted stability and more asymmetry in stability than other miRNAs in their respective clusters and the temperature-responsive strands represented the usually less abundant strand (Noland and Doudna 2013). However, the mechanisms for temperaturedependent strand selection, the reason for its restriction to so few miRNAs, and the extensive bias toward star strands remains incompletely understood.…”
Section: Figure 5 Functional Analysis Of the Pkcαmentioning
confidence: 99%